An optimized mode of interferon intermittent therapy help improve HBsAg disappearance in chronic hepatitis B patients - Li, Minghui; Xie, Si; Bi, Xiaoyue; Sun, Fangfang; Zeng, Zhan; Deng, Wen; Jiang, Tingting; Lin, Yanjie; Yang, Liu; Lu, Yao; Zhang, Lu; Yi, Wei; et al. (Frontiers in Microbiology, 2022)
BACKGROUND: To investigate the effect of intermittent interferon therapy mode on disappearance of hepatitis B surface antigen (HBsAg) in chronic hepatitis B (CHB) patients. METHODS: This is a retrospective cohort study in CHB patients who were suspended from pegylated interferon α (PEG-IFNα) therapy due to a plateau in HBsAg decline during the initial treatment period, and resumed interferon therapy after a 3-6 months interval. Patients received entecavir or tenofovir during the interval period. Hepatitis B virus (HBV) virological and serological indexes, clinical biochemical indexes and blood routine tests were performed at the baseline and every 3 months during follow-up of initial interferon treatment. Functional cure was analyzed as primary outcome. RESULTS: A total of 304 patients treated with intermittent PEG-IFNα were included in the statistical analysis, including 215 males and 89 females, aged 37.978.53 years, and 73 hepatitis B e antigen (HBeAg)-negative and 231 HBeAg positive patients. Fifty-nine patients (19.41%) achieved HBsAg disappearance through the initial, intermittent and retreatment of PEG-IFNα treatment,of whom 43 patients (14.14%) achieved HBsAg seroconversion. Early HBsAg response to initial treatment was significantly associated with HBsAg response at 12 and 24 weeks of retreatment. After the intermission period, the incidence of HBsAg disappearance in patients with early HBsAg response in the retreatment period was 43.87%. The baseline HBsAg and 12-week HBsAg response in the retreatment period had higher predictive value than the initial treatment HBsAg response. CONCLUSIONS: The initial, intermittent and retreatment mode of interferon can help to improve the HBsAg disappearance rate in CHB patients. Clinical trial registration number: NCT04028856.